AB0440 LDL-CHOLESTEROL AS A RISK FACTOR OF PROGRESSION TO ESRD IN PATIENTS WITH LUPUS NEPHRITIS. (2nd June 2020) - Park, D. J.; Choi, S. E.; Xu, H.; Kang, J. H.; Lee, S. S.
Abstract : Background: Objectives: There are few data on the effect of dyslipidemia in patients with lupus nephritis (LN). Thus, we investigated the effect of low-density lipoprotein-cholesterol (LDL-C) on the progression to end-stage renal disease (ESRD) in patients with biopsy-proven LN. Methods: We followed 121 LN patients who underwent kidney biopsy and were subsequently treated with immunosuppressive drugs. Sociodemographic, clinical, laboratory (including lipid profile), and treatment-related data at the time of kidney biopsy and during follow-up were obtained by a review of patients' charts. Patients were divided into two groups related to the mean LDL-C level: <100 mg/dL and ≥100 mg/dL. Cox's proportional regression analysis was performed to identify the independent predictors of progression to ESRD in LN patients. Results: Seventy-one of 121 biopsy-proven LN patients (58.7%) showed more than 100 mg/dL of LDL-C at the time of LN diagnosis. The higher LDL-C group excreted more 24-hour urine protein (p=0.003), and showed a higher proportion of proliferative LN (p=0.013) and an activity score >12 (p=0.023). During a mean follow-up of 83.0 (range, 12–171) months, ESRD was more frequent in the higher LDL-C group than in the lower group (15.5% vs. 2.0%; p=0.012). In the multivariate Cox's proportional regression analysis, LDL-C ≥100 mg/dL (hazard ratio [HR], 171.340; p=0.012), estimated glomerular filtration rate during the renal biopsy (HR, 0.977; p=0.005), statin exposure during follow-up (HR, 0.163; p=0.031), relapse (HR, 9.752; p=0.036), and complete remission at 1-year of treatment (HR, 0.034; p=0.003) were significant predictors of progression to ESRD in LN patients. Conclusion: Our findings suggest that dyslipidemia at the onset of LN is an independent risk factor for predicting the development of ESRD in LN patients. Therefore, lipid profile should be monitored carefully and managed aggressively to avoid the deterioration of kidney function in patients with LN. Disclosure of Interests: None declared